2018
DOI: 10.21764/maeuefd.364465
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarinin Akademi̇k Hi̇zmetlere İli̇şki̇n Görüşleri̇ Ve Memnuni̇yet Düzeyleri̇

Abstract: Özet: Bu araştırmanın amacı, öğretmen adaylarının bazı akademik hizmetlere ilişkin görüşlerini ve bu görüşlerle ilgili olabilecek değişkenler (cinsiyet, sınıf düzeyi, bölüm ve akademik not ortalaması ) ile öğrencilerin üniversiteye ve eğitim fakültesine yönelik memnuniyet düzeylerini incelemektir. Araştırmada, betimsel tarama modeli kullanılmıştır. Araştırmanın evrenini 2016-2017 öğretim yılında Trakya Üniversitesi Eğitim Fakültesi'nde öğrenim gören yaklaşık 2700 öğretmen adayı, örneklemini ise, üst sınıflarda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…It was found out in the present study that academic success is not related to being satisfied with the education program. Similar to the present study, it was found in the study by Donat-Bacıoğlu and Vural [16] that the opinions of students in faculty of education on academic services do not differ significantly according to academic grade average. Sert [28] also obtained similar results, although Ada, Baysal and Şahenk-Erkan [24] found out significant differences in the prospective teachers' perception of service quality in higher education according to their success levels in all subfactors.…”
Section: Results On the Change Of Satisfaction Levels Of Prospective supporting
confidence: 91%
See 1 more Smart Citation
“…It was found out in the present study that academic success is not related to being satisfied with the education program. Similar to the present study, it was found in the study by Donat-Bacıoğlu and Vural [16] that the opinions of students in faculty of education on academic services do not differ significantly according to academic grade average. Sert [28] also obtained similar results, although Ada, Baysal and Şahenk-Erkan [24] found out significant differences in the prospective teachers' perception of service quality in higher education according to their success levels in all subfactors.…”
Section: Results On the Change Of Satisfaction Levels Of Prospective supporting
confidence: 91%
“…In this sense, the satisfaction levels for the two studies in sub-dimensions show similarities. Donat-Bacıoğlu and Vural [16] concluded that the satisfaction levels of prospective teachers receiving training in Trakya University Faculty of Education regarding the university and faculty was "moderate", while Akdoğdu [17] also concluded that prospective primary school teachers evaluated the program as moderately sufficient. Similarly, Ceylan and Demirkaya [12] noted that prospective primary school teachers in their fourth year were moderately satisfied for each dimension of services provided by their universities and faculties.…”
mentioning
confidence: 99%
“…Similarly, in the study conducted by Özdemir et al (2018), a significant difference was found between critical thinking and programs, and in this study, it was concluded that GPC students were more critical than students in other programs. Gülveren (2007), Sakar and Aybek (2015) and Zayif (2008) found significant differences in the critical thinking levels of university students according to departments, and in many university satisfaction studies (Bacıoğlu & Vural, 2018;Şahin, 2009;Özdemir, Kılınç, Öğdem & Er, 2013), it was determined that there were differences in the satisfaction levels of students between programs. On the other hand, some studies (Özdemir, 2005;Erdem & Yazıcıoğlu, 2015) concluded that there was no significant difference in the critical thinking skills of university students according to the programs they studied.…”
Section: Discussionmentioning
confidence: 99%
“…kaynaştırma eğitim alma durumuna göre ise kaynaştırma yeterliliği arasında anlamlı bir farklılık tespit edilmemiştir. Söz konusu sonuçlar, geçmişteki pek çok araştırma (Karacaoğlu, 2008;Ekşi, 2010;Şahbaz ve Kalay, 2010;Sönmez ve arkadaşları, 2019) ile uyumludur. Ancak ilgili literatürde bazı çalışmalar da (Mağden ve Avcı, 1999;Sarı ve Bozgeyikli, 2002;Orel vd., 2004;Lancaster ve Bain, 2010;Dağlar, 2011;Güven ve Çelik, 2011), kaynaştırma eğitim alan öğretmenlerin, kaynaştırma almayan öğretmenlere göre kaynaştırma eğitimlerine ilişkin görüşlerinde farklılık olduğunu göstermektedir.…”
Section: Araştirmanin Bulgulariunclassified